1978
DOI: 10.1190/1.1440839
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Discrimination and Removal of Inductive Coupling With Multifrequency Ip

Abstract: In‐situ complex resistivity measurements over the frequency range [Formula: see text] to [Formula: see text] have been made on 26 North American massive sulfide, graphite, magnetite, pyrrhotite, and porphyry copper deposits. The results reveal significant differences between the spectral responses of massive sulfides and graphite and present encouragement for their differentiation in the field. There are also differences between the spectra of magnetite and nickeliferrous pyrrhotite mineralization, which may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
578
1
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(634 citation statements)
references
References 6 publications
7
578
1
14
Order By: Relevance
“…[65] Note, instead of using an additive combination of Cole-Cole terms, equation (44) can also be formulated in a multiplicative way [e.g., Pelton et al, 1978]. However, this would just affect the determined values of chargeability, which can easily be transformed into the chargeability values of the other formulation [e.g., Liu and Vozoff, 1985].…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…[65] Note, instead of using an additive combination of Cole-Cole terms, equation (44) can also be formulated in a multiplicative way [e.g., Pelton et al, 1978]. However, this would just affect the determined values of chargeability, which can easily be transformed into the chargeability values of the other formulation [e.g., Liu and Vozoff, 1985].…”
Section: Appendix Amentioning
confidence: 99%
“…This, however, would have to be done for each temperature and consequently represents a time-consuming procedure. Since we are interested here only in the EC response, we followed a much simpler approach and removed both MW polarization and EM effects from the spectral response by fitting a superposition of Cole-Cole functions to the data [e.g., Pelton et al, 1978;Major and Silic, 1981;Brown, 1985;Kemna et al, 2000], expressed in terms of complex resistivity as…”
Section: Data Processingmentioning
confidence: 99%
“…The evolution of calcite precipitation in porous media was clearly observed from their imaginary conductivity data. The empirical Cole-Cole model (Cole & Cole 1941;Pelton et al 1978) was used by Wu et al (2010) to interpret the complex conductivity signature of calcite precipitation on glass beads in terms of mean relaxation time and chargeability (capacity of the porous medium to store electric charges). At the early stage of the calcite precipitation experiment, Wu et al (2010) observed that the mean relaxation time and chargeability increase with time, and, after nine days of the experiment, they observed that the mean relaxation time and chargeability decrease with time.…”
Section: Introductionmentioning
confidence: 99%
“…Na escala macroscópica, vem relacionada com o tipo/espécie da fonte geradora do efeito e, através de uma função peculiar, ao seu teor na rocha (Pelton et al, 1978). Trata-se do parâmetro melhor estabelecido na literatura, na interpretação do efeito IP.…”
Section: O Modelo De Dias: Função "Condutividade Espectral" Ou De Counclassified
“…As possibilidades de aplicação da análise da "condutividade espectral", medida no laboratório ou no campo, ao estudo de temas de relevância na geofísica aplicada são várias, como por exemplo: distinção entre diferentes tipos e teores de minerais causadores da polarização, prospecção e caracterização de reservatórios deágua subterrânea, distinção entre litologias constituintes do meio geológico (como arenito, arenito argiloso, folhelho e rochas cristalinas), distinção entre zonas de formações geológicas preenchidas por fluidos diversos (comoágua,óleo ou gás), ou, ainda, variações do espaço intergranular das fontes geradoras do efeito IP no interior da matriz da rocha (Pelton et al, 1978;Olhoeft, 1985;Mahan et al, 1986;Lima, 1995;Dias, 2000;Lima et al, 2005;Dias et al, 2005Dias et al, , 2006. Outras aplicações, mais recentes, ainda não totalmente consolidadas, são a determinação in situ da permeabilidade e a distribuição espacial da dimensão dos poros da rocha em volume (Lima, 1995;Lima & Niwas, 2000;Maosong et al, 2004Maosong et al, , 2006aMaosong & Honggen, 2008).…”
Section: Introductionunclassified